Employees first, customers second : turning conventional management upside down. - Nayar, Vineet, ....- (Boston : Harvard Business Press, 2010)
One small idea can ignite a revolution just as a single matchstick can start a fire. One such idea, putting employees first and customers second, sparked a revolution at HCL Technologies, the IT services giant. In this candid and personal account, Vineet Nayar, HCLT's celebrated CEO, recounts how he defied the conventional wisdom that companies must put customers first, then turned the hierarchical pyramid upside down by making management accountable to the employees, and not the other way around. By doing so, Nayar fired the imagination of both employees and customers and set HCLT on a journey of transformation that has made it one of the fastest-growing and profitable global IT services companies and, according to BusinessWeek, one of the twenty most influential companies in the world. Chapter by chapter, Nayar recounts the exciting journey of how he and his team implemented the employee first philosophy by: Creating a sense of urgency by enabling the employees to see the truth of the company's current state as well as feel the "romance" of its possible future state, Creating a culture of trust by pushing the envelope of transparency in communication and information sharing, Inverting the organizational hierarchy by making the management and the enabling functions accountable to the employee in the value zone, Unlocking the potential of the employees by fostering an entrepreneurial mind-set, decentralizing decision making, and transferring the ownership of "change" to the employee in the value zone. Refreshingly honest and practical, this book offers valuable insights for managers seeking to realize their aspirations to grow faster and become self-propelled engines of change.